Design of low noise amplifier with active integrated antenna at 5 GHz - Peter, T. (IEEE, 2007)
An Active Integrated Antenna with Low Noise Amplifier (ALNA) at 5 GHz has been designed and developed for wireless communications. The design achieves a low noise figure by directly integrating a low noise amplifier to a dual layered microstrip close proximity coupled patch antenna at 5 GHz. Measured results show a noise figure (NF) of 1.22 dB, an excellent return loss of greater than 12 dB and good impedance matching which resulted in a bandwidth of about 10% for the active device. This paper presents the methodology, simulations and experimental works carried out in accomplishing the above objective. LINC2 and Microwave Office software were used to simulate and find the optimum design and results.